2021
DOI: 10.3390/ijerph18105213
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Online Version of the Alcohol Use Disorders Identification Test (AUDIT) for Alcohol Screening in Spanish University Students

Abstract: Online alcohol screening may be helpful in preventing alcohol use disorders. We assessed psychometric properties of an online version of the Alcohol Use Disorders Identification Test (AUDIT) among Spanish university students. We used a longitudinal online survey (the UNIVERSAL project) of first-year students (18–24 years old) in five universities, including the AUDIT, as part of the WHO World Mental Health International College Student (WMH-ICS) initiative. A reappraisal interview was carried out with the Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…After obtaining their informed consent, the students completed structured questionnaires. The main outcomes were ACEs and alcohol consumption by Alcohol Use Disorder Identification Test (AUDIT) ( Ballester et al, 2021 ). The questionnaire was compiled using Google Forms and distributed through the universities’ online systems, and data were extracted into an Excel spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After obtaining their informed consent, the students completed structured questionnaires. The main outcomes were ACEs and alcohol consumption by Alcohol Use Disorder Identification Test (AUDIT) ( Ballester et al, 2021 ). The questionnaire was compiled using Google Forms and distributed through the universities’ online systems, and data were extracted into an Excel spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
“…The AUDIT is a simple and effective method of detecting unhealthy alcohol use, defined as risky or dangerous consumption or any alcohol use disorder ( Daeppen et al, 2000 ; Kuitunen-Paul and Roerecke, 2018 ; Verhoog et al, 2020 ; Ballester et al, 2021 ). AUDIT can also help identify alcohol dependence and the specific consequences of harmful drinking.…”
Section: Methodsmentioning
confidence: 99%
“…However, several more recent studies have indicated that the cut-off score of 8 is suitable for males but too high for females, and have suggested differential cut-off scores for females of 5 (Aalto et al ., 2009 ) or 6 (e.g. Bergman and Kallmen, 2002 ; Aalto et al ., 2006 ; Ballester et al ., 2021 ), since women develop alcohol-related problems at lower levels of consumption than men (e.g. Bradley et al ., 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Alcohol Use Disorders Identifi cation Test (AUDIT) was used to determine alcohol consumption. AUDIT is used as one of the tools to detect alcohol consumption and related risk behaviours in primary care settings (25). AUDIT is a 10-item clinical screening tool with a score ranging from 0 to 40 (26,27).…”
Section: Alcohol Use Disorders Identifi Cation Test (Audit)mentioning
confidence: 99%